The Influence of Marketing Mix on Aice Ice Cream Purchase Decision in Balikpapan: Marketing mix - Erlimisnawati, Erlimisnawati; Prihandoyo, C.; Hermawansyah, Adi (SEAN Institute, 2024)
This research is aims to determine the impact of the marketing mix on the purchasing decisions of Aice ice cream in Balikpapan. The study was conducted at PT. Shunli Aneka Food and Aice outlets in Balikpapan with 385 respondents. This research utilized a quantitative method. Data collection was carried out by distributing questionnaires directly. The data analysis technique in this study was multiple linear regression analysis, including testing the instrument, classical assumption tests, and hypothesis testing partially (t-test). The results of the multiple linear regression analysis indicate that the product, price, promotion, and location have a positive and significant influence on purchasing decisions, both partially and simultaneously.